Analysis of factors associated with the first lumpy skin disease outbreaks in naïve cattle herds in different regions of Thailand - Arjkumpa, Orapun; Wachoom, Wanwisa; Puyati, Bopit; Jindajang, Sirima; Suwannaboon, Minta; Premashthira, Sith; Prarakamawongsa, Tippawon; Dejyong, Tosapol; Sansamur, Chalutwan; Salvador, Roderick; Jainonthee, Chalita; Punyapornwithaya, Veerasak (Frontiers in Veterinary Science, 2024)
Thailand experienced a nationwide outbreak of lumpy skin disease (LSD) in 2021, highlighting the need for effective prevention and control strategies. This study aimed to identify herd-level risk factors associated with LSD outbreaks in beef cattle herds across different regions of Thailand. A case-control study was conducted in upper northeastern, northeastern, and central regions, where face-to-face interviews were conducted with farmers using a semi-structured questionnaire. Univariable and multivariable mixed-effect logistic regression analyses were employed to determine the factors associated with LSD outbreaks. A total of 489 beef herds, including 161 LSD outbreak herds and 328 non-LSD herds, were investigated. Results showed that 66% of farmers have operated beef herds for more than five years. tThere were very few animal movements during the outbreak period. None of the cattle had been vaccinated with LSD vaccines. Insects that have the potential to act as vectors for LSD were observed in all herds. Thirty-four percent of farmers have implemented insect control measures. The final mixed-effect logistic regression model identified herds operating for more than five years (odds ratio [OR]: 1.62, 95% confidence interval [CI]: 1.04-2.53) and the absence of vector insect control management on the herd (OR: 2.05, 95% CI: 1.29-3.25) to be associated with LSD outbreaks. The implementation of insect-vector control measures in areas at risk of LSD, especially for herds without vaccination against the disease, should be emphasized. This study provides the first report on risk factors for LSD outbreaks in naïve cattle herds in Thailand and offers crucial useful information for the development of LSD prevention and control programs within the country's context.